Peningkatan Industri Rumah Tangga Krupuk Tangguk Berbahan Dasar Ketela Pohon Di Kelurahan Gladak Anyar Pamekasan - Nuriyanti, Ika; Umi Kalsum; Junaidi; Ingsih, Ita Suhermin (Direktorat Penelitian dan Pengabdian kepada Masyarakat (DPPM), 2022)
Pamekasan area is famous for its crackers called krupuk tangguk. The industrial center area in Gladak Anyar Village is able to absorb 30 to 60 workers. IRT Ã¢â‚¬Å“SINABÃ¢â‚¬Â which is used as an activity partner, has several problems, including: low attention to the type of raw material so that the taste of the product is not standard; the drying area uses a base made of woven coconut leaves so that the product is not hygienic; the frying process still uses firewood, frying oil is used until it turns black and there has been no attempt to purify the oil causing low product quality, there has been no effort to product packaging and labeling, financial management is unwell documented, and product brands have not been registered with the Directorate General of Intellectual Property Rights. These problems will be resolved by providing training on the importance of selecting raw materials, training on cooking oil purification, training in making financial journals, registering trademarks and providing equipment assistance such as stoves replaced with LPG and LPG gas stoves, drying places for crackers from woven leaves. coconut replaced tools made of stainless steel, packaging and labeling devices. The output targets of this program are tangguk crackers with better quality and performance, registered trademarks, and produce a good financial management system.